Pengaruh Faktor Psikologis dan Dukungan Organisasi terhadap Kinerja Perawat di Rumah Sakit Umum Lukas Hilisimaetano Teluk Dalam Nias Selatan Tahun 2018 - apriani krista witer laia apriani (Jurnal Maternitas Kebidanan, 2020)
ABSTRACT. Nursing committee report on the performance of nurses in completing nursing service documents reached 33.5% (2010 files) from 6,000 files in 2017. The number of nurses who have certification is 30% (36 nurses) out of 120 nurses. The still low completeness of nursing service documents is one of the nurses' performance in providing nursing care. The research objective was to analyze the influence of psychological factors (knowledge, attitudes, and motivations) and organizational support (training and development, facilities, interpersonal relationships) on the performance of nurses in the Lukas Hilisimaetano General Hospital in Teluk Dalam, South Nias in 2018. The type of this research is an analytic survey with an approach cross sectional. The population was all nurses who worked at Lukas Hilisimaetano General Hospital in Teluk Dalam, South Nias, with 120 people and 92 samples. Data were analyzed univariately, bivariate using chi-square and multivariate using multiple logistic regression tests at a significance level of 5%. The results showed psychological factors of nurses were categorized were not good (56.5%), organizational support factors were not good (58.7%) and nurses' performance was good (54.3%). Psychological factors (p 0.012), and organizational support (p 0.002) affect the performance of nurses. Organizational support factor Exp (B) value of 4,599 more strongly influences nurses' performance than psychological factors. It is recommended to hospital management in improving nurse performance by providing opportunities for training, seminars, further education to improve abilities and skills. Propose criteria for the size of the incentives and rewards received based on the nurse's performance and evaluate the nurse's performance continuously. Keywords: Psychological, Organizational Support, Nurse Performance